2016
DOI: 10.1007/s00277-016-2689-8
|View full text |Cite
|
Sign up to set email alerts
|

A new extranodal scoring system based on the prognostically relevant extranodal sites in diffuse large B-cell lymphoma, not otherwise specified treated with chemoimmunotherapy

Abstract: Extranodal involvement is a well-known prognostic factor in patients with diffuse large B-cell lymphomas (DLBCL). Nevertheless, the prognostic impact of the extranodal scoring system included in the conventional international prognostic index (IPI) has been questioned in an era where rituximab treatment has become widespread. We investigated the prognostic impacts of individual sites of extranodal involvement in 761 patients with DLBCL who received rituximab-based chemoimmunotherapy. Subsequently, we establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…33, 34 This study, enrolling the largest number of de novo DLBCL patients with positive BM involvement to date, allowed valuable and effective analysis and confirmed that there is heterogeneity in the positive BM cohort.…”
Section: Discussionmentioning
confidence: 59%
“…33, 34 This study, enrolling the largest number of de novo DLBCL patients with positive BM involvement to date, allowed valuable and effective analysis and confirmed that there is heterogeneity in the positive BM cohort.…”
Section: Discussionmentioning
confidence: 59%
“…3 Conversely, as the most common extranodal site, GI tract involvement indicated favorable prognosis, which remains controversial among previous studies. 3,28,29 As for genetic alterations, we provided genomic evidence corresponding to clinical data in extranodal DLBCL. Oncogenic mutations were frequently observed in patients with lymphoma invasion of the bones, kidney/adrenal glands (MYD88), 30 spleen (BCL6, IRF8, KMT2D, and SOCS1), [31][32][33][34] lungs (FAS and NFKBIE), 35,36 and liver (BCL6), 31 but less often in patients with GI invasion (MYD88, PIM1, MEPG1, DUSP2, and HIST1H1E).…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] However, the International Prognostic Index (IPI), which was developed in the era of chemotherapy treatment for aggressive lymphoma, has proven to be less powerful in the rituximab era. To better distinguish tumor prognosis, several models [ 4 , 5 ] and algorithms [ 6 , 7 ] have been developed. In addition, several markers have been discovered in DLBCL, to better identify patients who will likely have a poor therapeutic response.…”
Section: Introductionmentioning
confidence: 99%